2023
DOI: 10.3389/fbioe.2023.1128934
|View full text |Cite
|
Sign up to set email alerts
|

A novel electrochemical IL-6 sensor based on Au nanoparticles-modified platinum carbon electrode

Abstract: Introduction: Interleukin-6 (IL-6) is a multifunctional polypeptide cytokine composed of two glycoprotein chains, which plays an important role in many cellular reactions, pathological processes, diagnosis and treatment of diseases and so on. The detection of IL-6 plays a promising role in the cognition of clinical diseases.Methods: 4-mercaptobenzoic acid (4-MBA) was immobilized on the gold nanoparticles modified platinum carbon (PC) electrode with the linker IL-6 antibody, and finally formed an electrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In addition to this, hydrazine has also been extensively used in several industrial and agricultural applications; however, its prolonged exposure makes it neurotoxic, carcinogenic, mutagenic, hepatotoxic, and nephrotoxic to humans and also pollutes the environment [ 27 ]. It is also reported that an increase in the hydrazine level beyond its critical standards could cause adverse effects, hence its level should be monitored [ 28 , 29 , 30 ]. Until now, fluorescence, chemiluminescence, chromatographic, spectroscopic, and electrochemical approaches have been used to detect N 2 H 4 [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, hydrazine has also been extensively used in several industrial and agricultural applications; however, its prolonged exposure makes it neurotoxic, carcinogenic, mutagenic, hepatotoxic, and nephrotoxic to humans and also pollutes the environment [ 27 ]. It is also reported that an increase in the hydrazine level beyond its critical standards could cause adverse effects, hence its level should be monitored [ 28 , 29 , 30 ]. Until now, fluorescence, chemiluminescence, chromatographic, spectroscopic, and electrochemical approaches have been used to detect N 2 H 4 [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical-sensing technique has recently gained popularity for its rapid detection of trace amounts of hazardous compounds in aqueous media. In addition to this, its excellent specificity, low cost, and quick response for detecting a wide range of analytes makes it an appealing method for analyzing the content of a sample by directly converting the response into an electrical signal [ 30 , 33 ]. Some reports suggest that by incorporating nanomaterials, the electrochemical response shows better sensitivity and limits of detection and improves their robustness.…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 is a pleiotropic cytokine polypeptide which can produce by various cells such as lymphocytes, endothelial cells, keratinocyte, neural cells, and bone cells, under stimulation by special inducers and at the site of inflammation [ 5 , 6 ]. Knowing the structure of IL-6 is important in analyzing its detection processes, as its properties such as isoelectric point (pI) and molecular mass affect its sensing function.…”
Section: Introductionmentioning
confidence: 99%